APPLICATION OF CLUSTER ANALYSIS TO STUDY COMPETITIVE ENVIRONMENT IN THE KNITWEAR MARKET - Radjabov Bunyod Abduhalilovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
The article explores the theories of using cluster analysis in marketing research, based on the importance and necessity of exploring the competitive environment in the knitwear market. Competitive environment in the knitwear market of the Republic of Uzbekistan has been studied using cluster analysis. The effectiveness of cluster analysis of competitive environment in the knitwear market is demonstrated.